2012
DOI: 10.1002/chem.201102677
|View full text |Cite
|
Sign up to set email alerts
|

ansa‐Rare‐Earth‐Metal Catalysts for Rapid and Stereoselective Polymerization of Renewable Methylene Methylbutyrolactones

Abstract: Two ansa-half-sandwich rare-earth-metal (REM) dialkyl complexes supported by an ethylene-bridged fluorenyl (Flu)-N-heterocyclic carbene (NHC) ligand, [M{C(2)H(4)(η(5)-Flu-κ(1)-NHC)}(CH(2)SiMe(3))(2)] (M=Y, 1; Lu, 2), and a chiral ansa-sandwich samarocene incorporating a C(2) ligand, [Sm(η(5)-C(12)H(8))(2)(thf)(2)] (3), have been investigated for the coordination-addition polymerization of renewable methylene butyrolactones, α-methylene-γ-butyrolactone (MBL) and γ-methyl-α-methylene-γ-butyrolactone ((γ)MMBL). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 83 publications
2
54
0
Order By: Relevance
“…The assignments of the triads were based on the backbone quaternary carbon resonances, following the literature. 5 Computational Details. Calculations followed the procedures described in our prior publications.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The assignments of the triads were based on the backbone quaternary carbon resonances, following the literature. 5 Computational Details. Calculations followed the procedures described in our prior publications.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The 1 H nuclear magnetic resonances (NMR) of the polymers were too broad to unravel the tacticity of the polymer, and no T g was reported. A later study showed that the polymer by radical initiation was essentially atactic (27,45). The study of the polymerization kinetics revealed that the rate of polymerization (R p ) followed the kinetic expression R p = k[AIBN] 0.54 [ β MMBL] 1.04 .…”
Section: Free-radical Polymerizationmentioning
confidence: 99%
“…Chemically, MBL can be produced from biomass sugar-based itaconic anhydride (20), whereas γ MMBL can be readily prepared via a two-step process developed by DuPont (21,22) from the biomass-derived levulinic acid, which is produced at 450 tons/year (23). β MMBL is currently prepared by a multistep synthesis (24,25) but can be potentially prepared from condensation of 3-methyl-γbutyrolactone, available from hydrogenation of the biomass-derived itaconic acid (26), with formaldehyde (27). These biomass-derived methylene butyrolactones are of special interest in exploring the outlook of substituting the petroleumbased methacrylate monomers for specialty chemicals production (14,28).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations